Financial Aberrations of Rural Customers of Business Correspondents: Characteristics, Cases and Curative Strategies - Dhar, Samirendra Nath; Jaiswal, Pintu Prasad (International Journal of Social Sciences and Management, 2021)
Financial Inclusion through Business Correspondents is not free from financial aberrations. On the basis of some cases the paper investigated into the types and frequency of the financial aberrations, which are incident on customers .The magnitude of shocks as perceived by the BC customers due to the financial process aberrations and irregularities were gauged on a Likert scale and was found to be significantly high. As these shocks have a bearing on financial resilience, the research further attempted to investigate whether awareness of dealing with the system and thereby increasing financial resilience could be developed through financial literacy programs. A longitudinal research design was adopted and 17-18% of the male and female respondents from each district were exposed to a financial literacy programme in this context as devised by the researchers. It was found that the administration of the program on poor BC customers had a significant positive effect on their awareness and therefore on their build-up of financial resilience. Int. J. Soc. Sc. Manage. Vol. 8, Issue-3: 401-407.